Data citizenship: Rethinking data literacy in the age of disinformation, misinformation, and malinformation - Elinor Carmi; Simeon J. Yates; Eleanor Lockley; Alicja Pawluczuk (Internet Policy Review, 2020)
In this paper we examine what "data literacy" - under various definitions - means at a time of persistent distribution of "dis-/mis-/mal-information" via digital media. The paper first explores the definition of literacies (written, media, information, digital and data literacies) considering the various parameters and considerations they have gone through. We then examine the intersection of dis-/mis-/mal-information and "fake-news" and these literacies. The paper explores what types of literacies are needed today and the important role of variations in citizens' social context. We highlight three main gaps in current data literacy frameworks - 1. going beyond the individual; 2. critical thinking of the online ecosystem; and 3. designing skills for proactive citizens. We discuss these gaps while highlighting how we integrated these into our survey of UK citizens' data literacies as part of our Nuffield Foundation funded project - Me and My Big Data. By discussing our theoretical and methodological challenges we aim to shed light on not only how the definition of data literacy changes but also how we can develop education programmes that take into account information distortions and put proactive citizens at the centre.
Keywords: 300; Data literacy; Literacy; Disinformation; Misinformation; Fake news; Networks of literacy